2018
DOI: 10.1016/j.cobeha.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Linking anhedonia symptoms with behavioural and neural reward responses in adolescent depression

Abstract: Adolescence is a period of change that crucially increases vulnerability to depression. Studies report blunted neural responses to reward that relate to positive affect and depression symptoms in adolescents. However how these results relate to the symptom of anhedonia in adolescents is not entirely clear. Anhedonia is not a unitary construct, but is described as having different processes (e.g. wanting vs. liking) each underpinned by different neurobiological pathways. Current studies report inconsistencies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 97 publications
(109 reference statements)
1
29
0
1
Order By: Relevance
“…However, most studies assess anhedonia using only a few questions within other questionnaires such as the Beck Depression Inventory and do not provide a comprehensive understanding of the experience of anhedonia on a dimensional scale. 9 Therefore we suggest using assessments such as the Temporal Experience of Pleasure Scales (TEPS) that allow for the separate components of anhedonia (anticipation and consummation) to be measured. 9,10 Neurobiological studies have found blunted neural reward responses that relate to positive affect 11 and depression symptoms in adolescents 12,13 and even young children.…”
Section: Anhedonia Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most studies assess anhedonia using only a few questions within other questionnaires such as the Beck Depression Inventory and do not provide a comprehensive understanding of the experience of anhedonia on a dimensional scale. 9 Therefore we suggest using assessments such as the Temporal Experience of Pleasure Scales (TEPS) that allow for the separate components of anhedonia (anticipation and consummation) to be measured. 9,10 Neurobiological studies have found blunted neural reward responses that relate to positive affect 11 and depression symptoms in adolescents 12,13 and even young children.…”
Section: Anhedonia Assessmentmentioning
confidence: 99%
“…9 Therefore we suggest using assessments such as the Temporal Experience of Pleasure Scales (TEPS) that allow for the separate components of anhedonia (anticipation and consummation) to be measured. 9,10 Neurobiological studies have found blunted neural reward responses that relate to positive affect 11 and depression symptoms in adolescents 12,13 and even young children. 14 However, most neurobiological tasks of reward do not examine the different phases of processing such as the anticipatory, motivational and consummatory aspects.…”
Section: Anhedonia Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with adult depression described above, there is a heterogeneity in symptoms of adolescent depression and it is not entirely clear how they map to neurobiology [6]. One reason for this has been inconsistent use of questionnaires and assessments in research, which lack any specific detail about mood change in depression [7]. Understanding adolescent depression could benefit from more detailed measures of specific symptoms, e.g., anhedonia (the reduced experience of interest and pleasure), which is currently usually only assessed via its presence or absence and not in any detail from the adolescent experience [7].…”
Section: Adolescent Depressionmentioning
confidence: 99%
“…Of particular interest, structural alteration (e.g., volumetric changes) in subcortical regions including the amygdala, hippocampus, and NAcc has been known to be associated with both social stress and psychopathology 9,10 . This may be because these regions have been implicated in social and emotion processing and reward-punishment processing 11,12 . These regions are also known to be sensitive to social stress 13 , and continue to develop throughout the adolescence 14 .…”
mentioning
confidence: 99%